In service of their communities : public libraries today - Horvat, Aleksandra knjižničarka (Array, 2011)
Public libraries are societal institutions that genuinely mirror the society in which they have been set up. In spite of the fact that they are normally established and funded by the local communities, their activities reflect the broader policies of a particular society towards its citizens. The contemporary society in which public libraries act today has been characterized by specific, highly prominent traits, which strongly influence the libraries' activities and have to be taken into account in any discussion on libraries. The article deals with those traits and an attempt is made to determine the future strategy of public libraries in Croatia.